Sintesis Komposit N-TIO2/Bentonit dan Karakterisasi Menggunakan FTIR - Emas Agus Prastyo Wibowo (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2017)
AbstractTitanium Dioxide (TiO2) is a semiconductor material that is relatively inert compared with other compounds, and also serves as a photocatalyst which has fotoaktifitas and high stability. The presence of dopant N on TiO2 matrix will reduce the band gap of TiO2 so that shift the absorption spectrum from UV to visible light that are abundant in sunlight. Besides the addition of dopants on TiO2 matrix, the addition of bentonite can also increase the photocatalytic activity of TiO2. The main absorption peak-uptake at N-TiO2/ bentonite is still the same with bentonite which is in wavenumber 3626.17 cm-1, 3448.72 cm-1 and 1635.64 cm- Based on the interpretation of the spectra of FT-IR composite of Bentonite, TiO2 /bentonite, and N-TiO2/ bentonite produced can be concluded that no significant changes between the functional groups and bentonite as composite TiO2-bentonite and N-TiO2 / Bentonite Keywords: FTIR, composite, titanium dioxide AbstrakTitanium Dioksida (TiO2) merupakan bahan semikonduktor yang relatif inert dibandingkan dengan senyawa-senyawa lain dan juga berfungsi sebagai fotokatalis yang memiliki fotoaktifitas dan stabilitas tinggi. Adanya dopan N dalam matriks TiO2 akan memperkecil band gap TiO2 sehingga terjadi pergeseran penyerapan spektrum sinar dari sinar UV ke sinar tampak yang tersedia melimpah dalam sinar matahari. Selain dengan penambahan dopan pada matriks TiO2, penambahan bentonit juga dapat meningkatkan aktifitas fotokatalitik dari TiO2. Puncak serapan-serapan utama pada N-TiO2/bentonit masih sama dengan bentonit yang berada di bilangan gelombang 3626.17 cm-1, 3448.72 cm-1 dan 1635.64 cm-1. Berdasarkan interpretasi spektra FT-IR komposit dari Bentonit, TiO2/bentonit, dan N-TiO2/bentonit yang dihasilkan dapat disimpulkan bahwa tidak terjadi perubahan gugus fungsi yang signifikan antara bentonit sebagai dan komposit TiO2-Bentonit dan N-TiO2/Bentonit. Kata kunci: FTIR, komposit, titanium dioksida